Glutamate ionotropic receptor AMPA type subunit 1 gene polymorphism (Gly>Ser) and its association with schizophrenia in Pakistani population: A pilot Study. - Javed, Ariba; Batool Malik, Ayesha; Amir, Qurat-ul-Ain; Hanif , Farina; Washdev; Jawed, Lalarukh (International Journal of Endorsing Health Science Research, 2021)
Background: Neurobiology of schizophrenia involves impairment of glutamatergic neurotransmission. In this context, polymorphism in glutamate Ionotropic receptor a-amino-3-hydroxy-5-methyl-4-propionic acid (AMPA) type subunit 1 encoded by Glutamate Ionotropic Receptor AMPA Type Subunit 1 Gene (GRIA), (rs1127386, G/A) can be considered as a substantial contributor in pathogenesis of schizophrenia. Therefore, a pilot study was planned to find out if the single nucleotide polymorphism of GRIA (rs1127386, G/A) is a risk factor for schizophrenia in the population of Pakistan. It maps at 5q33, a schizophrenia susceptible locus as per genome-wide association studies. Methodology: Following Diagnostic and Statistical Manual 5 (DSM 5) criteria guidelines, 50 schizophrenia cases were incorporated in this case-control study and 51 controls, individuals without any psychiatric illness. The sternness of illness was figured out using positive and negative syndrome scale score (PANSS) score. Genomic DNA was extracted from blood, and further analysis was done on gel electrophoresis after conducting ARMS (amplification refractory mutation system) PCR. Frequencies of reported genotype and allele within both groups were determined using the chi-square test. Results: Statistically significant difference was not found in genotype and allele frequencies of (rs1127386, G/A) (p>0.05) between cases and controls in the study population. The severity status of the disease was also independent of the polymorphism (p>0.05). Conclusion: This pilot study specifies that polymorphism rs1127386 is not a risk factor for schizophrenia, at least in the Pakistani population.